Citizen Journalism (Jurnalisme Warga): Dari Fakta Berita dan Profesionalitas - R. Firdaus Wahyudi (LP2M IAI Muhammadiyah Sinjai, 2020)
Citizen journalism or citizen journalism where its presence is a response to internet-based or digital communication technology which is often also known as new media. With its various platforms, the new media provides space for each individual to carry out activities that have always been carried out by conventional media journalists or professional journalism. Citizen journalism is an individual activity related to the acquisition, management and dissemination of events, facts or incidents in the form of news delivered through social media. News or information is a manifestation of the processing of an event, data or fact which always involves elements of perspective and interest values, but of course it must not neglect the standards of professional news making. Besides that, citizen journalism must always be required to work in the corridor of professionalism which is reflected in the applicable journalistic code of ethics. This research is a qualitative research through literature study related to citizen journalism. The results of this research are that citizen journalism is an activity of citizens who are involved in the world of journalism or news delivery, citizen journalism work is required to comply with the standards of news making and professional journalism work, however under the legal umbrella, citizen journalism does not have a legal umbrella like professional journalism.